Direct Benefit Transfer: The Great Technological Move of India - Showkat ahmad dar (International Journal of Information Technology and Education, 2022)
DBT has been used to deliver over 450 schemes to over 900 million people. Since 2016, the government has deposited nearly 65% of the welfare and subsidy budget directly into beneficiaries' accounts. DBT will undoubtedly meet the government's and people's expectations, especially those of the poor and unfortunate. We hope that more schemes will be covered by DBT, and that the entire country and its people will receive benefits without delay or flaws. As a result, the government must make a concerted effort in various areas of planning to improve the lives of the poor and powerless in society. In this way, DBT helps create an environment where people can live long, healthy, and creative lives. This paper examines the role of Direct Benefit Transfer.